Facile one-pot synthesis of 5-aryl/heterylidene-2-(2-hydroxyethyl- and 3-hydroxypropylamino)-thiazol-4-ones via catalytic aminolysis. Issue 11 (3rd June 2017) - Golota, Sergii; Sydorenko, Ivan; Surma, Roman; Karpenko, Olexandr; Gzella, Andrzej; Lesyk, Roman
ABSTRACT: A multicomponent synthetic approach for 5-aryl/heterylidene-2-(2-hydroxyethylamino)- and 2-(3-hydroxypropylamino)-thiazol-4-ones starting from 2-thioxothiazolidin-4-one or 2-methylsulfanylthiazol-4-one was developed. The proposed method involves simultaneous aminolysis of 2-thioxo- or 2-methylsulfanyl groups and Knoevenagel condensation with (hetero)aromatic aldehydes using 2-aminoethanol or 3-aminopropan-1-ol as catalysts. Side-chain prototropic amino–imino tautomerism was observed for target 5-ylidene-2-alkylaminothiazol-4-ones. GRAPHICAL ABSTRACT: